Współpraca transgraniczna w regionie Morza Bałtyckiego na przykładzie projektu Defris - Sadowska, Karolina (Trans-border Cooperation in the Baltic Region Based on the Defris Project, 2006)
For achieving the goals cohesion policy activities which involve in cooperation different partners from different countries are particularly important, because they have wide knowledge and experience. Project Defris is the example of such cooperation realized by Kujawsko-Pomorskie voivodship which cooperates with partners from Sweden, Finland and Lithuania. The purpose of the project is the realization of common activities focused on long-lasting, constant development and achieving social, economic and territorial cohesion of the Baltic Sea region. The possibility of cooperation in this project allows the participants to find the best solution which guarantees the best effect with acceptable level of costs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 450-458